Seoul as Cinematic Cityscape: Shiri and the Politico-Aesthetics of Invisibility. Issue 2 (1st September 2000) - Diffrient, David Scott
In his recent book, Hong Kong: Culture and the Politics of Disappearance, Ackbar Abbas charts the complex spatial coordinates of a port city that, leading up to its 1997 "handover" to China, endured colonial "dislocations and discontinuities." Though Abbas focuses on the cultural forms unique to Hong Kong that melt away either "local, " "marginal, " or "cosmopolitan" identities and, in the space of that evaporation, reveal the dynamic symbiosis between colonialism and globalism, his attempt to destabilize the traditional fallacies of identity-construction can be superimposed atop virtually any city rendered historically anomalous during the reign of late capitalism.